Polsko-śląsko-niemieckie Szybolety w rejonie Śląska Cieszyńskiego - Kowalczyk, Andrzej (Językowe, literackie i kulturowe refleksje na temat jedności w różnorodności, 2023)
Originating in the Old Testament, the word shibboleth is a term used for phonetic identification marks of a certain language or Dialect, which can be used for distinguishing between their native users and people without the ability to use them fluently. Some sounds, words or even whole phrases were used in History to distinguish locals from outlanders in domestic situation as well as crisis times in form of conflicts or pogroms. Shibboleths are a natural Phenomenon existing due to the local evolution of languages, however they may be used for discrimination. The region of Cieszyn Silesia is characterised by a huge diversity in the area of language, because in the local dialect, which is one of the polish dialects, there is a strong Czech and German influence. Some of its phenomena, like the jabłonkowanie, may be seen as schibboleth and used for distinguishing the Cieszyn Silesian dialect users from the users of other Silesian dialects and natives in the neighbour languages.